Progressivity of Judges in Domestic Violence Disputes Settlement in The Case of Divorce in The Religious Court - Nita Triana (Sultang Agung Islamic University, 2018)
This study aims to describe and analyze the Judge Progressiveness in the case of a divorce related to domestic violence. The principle of law governing civil judges is passive, in reality this principle creates difficulties for women (wives) victims of domestic violence to achieve justice. The research method used is non-doctrinal tradition with a socio-legal approach, and qualitative descriptive analysis. The results of the study illustrate. Religious Courts Judges as one of the law enforcers are very potential to seek justice for victims of domestic violence, the majority of whom are women, because many cases of domestic violence ended in divorce cases in the Religious Courts. But the consideration of the religious Court Judge in deciding the case of a divorce petition is not yet progressive, the Judge still adheres to the principle of law, that the Civil Judge is passive. So that when the Plaintiff (Wife) does not demand income and compensation from her husband. The Plaintiff (Wife) as a victim of domestic violence will not get a living idah, mut'ah, maskan, kiswah and any compensation from the Defendant (Husband). Religious Court Judges have not yet explored other relevant legislation, including progressive religious texts that favor women as victims of domestic violence to strengthen the building of their arguments. Whereas in the case of divorce by talak, the Judge views the law in book in his legal considerations by giving protection to the wife, namely by giving the wife the right to earn a living Idah, Mutah (a living for one year to entertain the wife divorced by her husband), maskan and kiswah, according with what is stipulated in the Marriage Law and the Compilation of Islamic Law. The paradigm of the operation of the Judge in a country with a pluralistic culture such as Indonesia, it's time to change to a more progressive direction, Judge is no longer limited to the existence of a mouth that sounds the sentence of the law ( le judge est uniquenment la bouche qui pronance le most de lois) Judge also not tools designed to be logical and work mechanically, but whole people who have sensitivity to humanitarian and social concerns. Progressive judges learn and are good at making interpretations that are not literal (connotative), and have a high sense of empathy to be able to catch social norms that contextually support each prescription of the Act. The holistic understanding of the judges has the potential to provide justice for women victims of domestic violence.